2020
DOI: 10.11604/pamj.2020.37.198.25294
|View full text |Cite
|
Sign up to set email alerts
|

Lost to follow up rate in the first year of ART in adults initiated in a universal test and treat programme: a retrospective cohort study in Ekurhuleni District, South Africa

Abstract: Introduction South Africa adopted and implemented the Universal Test and Treat (UTT) strategy for HIV since 2016. However, the care outcomes for patients initiated antiretroviral therapy (ART) through the UTT strategy have not been established. We determined the rate of lost to follow up (LTFU) and associated factors in patients who were initiated on ART through the UTT and the pre-ART strategy at 12 months post ART initiation. Methods this retrospective study analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 41 publications
2
30
1
Order By: Relevance
“…We have no reason to suspect that this limitation would have affected our study arms differentially, however. While rates of loss to follow‐up in our study were high, they were not outside the bounds reported by other studies [ 19 , 20 ]. Loss to follow‐up and treatment interruptions during the first year after starting ART are common throughout the sub‐Saharan region and are a critically important challenge for the success of national ART programmes [ 21 ].…”
Section: Resultscontrasting
confidence: 73%
“…We have no reason to suspect that this limitation would have affected our study arms differentially, however. While rates of loss to follow‐up in our study were high, they were not outside the bounds reported by other studies [ 19 , 20 ]. Loss to follow‐up and treatment interruptions during the first year after starting ART are common throughout the sub‐Saharan region and are a critically important challenge for the success of national ART programmes [ 21 ].…”
Section: Resultscontrasting
confidence: 73%
“…The impact of the implementation of the TA strategy on retention is debated. Some authors showed no influence on retention [6], while others reported a positive [20,35] or a negative impact [11,18,52,53]. Importantly, we demonstrated that the implementation of the TA strategy significantly modified the clinical characteristics of PLWH on ART toward a greater proportion of men, a higher CD4 cell count and a lower clinical WHO stage at treatment initiation.…”
Section: Plos Global Public Healthmentioning
confidence: 59%
“…Intensive supportive interventions need to address retention in care issues for patients initiating ART in the context of the TA strategy. In addition, different patient tracing strategies, such as SMS reminders, phone calls and home visits, would limit attrition [32,53].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Although few studies have evaluated the effect of universal treatment on long-term retention, studies published since 2019 have shown that 12 months retention following universal treatment is below that required for viral suppression, highlighting the need for targeted interventions to ensure long-term sustainability. 4,5 Many national programmes are scaling up alternative service delivery approaches, known as differentiated service delivery models, to cope with the growing number of people with HIV on treatment. 6 A range of differentiated service delivery models focusing on people with stable disease have been successfully implemented in sub-Saharan Africa allowing them to engage in care through on-going adherence support and dispensation of prepacked medications by community health workers.…”
Section: Introductionmentioning
confidence: 99%
“…Although few studies have evaluated the effect of universal treatment on long-term retention, studies published since 2019 have shown that 12 months retention following universal treatment is below that required for viral suppression, highlighting the need for targeted interventions to ensure long-term sustainability. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%